One-pot green synthesis of zinc oxide nanoparticles using Morus laevigata aqueous extract and evaluation of its anticancer potential against HT-29 cell line - Paranthaman Sathishbabu; Shivakumar C. S.; Kalaipriya S.; Venkatesh Hosur Narayanappa; Gireesha J.; Pasha Shuaib; Shazly Gamal A.; Anandan Satish; Shivamallu Chandan; Kollur Shiva Prasad (Main Group Metal Chemistry)
Colon cancer presents significant challenges in treatment efficiency and patient outcomes, necessitating innovative, effective strategies due to the adverse effects of conventional therapies. The study aimed to investigate the green synthesis of zinc oxide nanoparticles (ZnO NPs) using aqueous extract of Morus laevigata (ML) leaves and their potential biomedical applications. ML-ZnO NPs were characterized using analytical techniques. The absorption band at 330 nm was detected by UV–Vis spectroscopy, confirming the formation of ML-ZnO NPs. An average size of 68.5 ± 1.85 nm and a negative zeta potential of −11.1 ± 0.98 mV confirm the stability of nanoparticles in colloidal solutions. FTIR analysis confirmed ML-ZnO NPs, with absorption bands corresponding to Zn–O stretching vibrations and aliphatic CH and CH2 groups. SEM examination revealed diverse patterns including cauliflower-like formations. Further anticancer activity of ML-ZnO NPs was assessed through cell viability, cell cycle, and apoptosis assays. ML-ZnO NPs inhibited HT-29 cell growth dose dependently, exceeding cisplatin 56.33 ± 0.87% cell viability. Cell cycle arrest at the G2M phase in HT-29 cells treated with ML-ZnO NPs was noticeable, further validated by apoptosis, which showed large increases in apoptotic cell populations. These results may pave the way for future research investigating the potency of ZnO NPs derived from plant extracts to manage colon cancer.